Preparation and Characterization of Encapsulated Cymbopogon citratus Essential Oils in Alginate/Chitosan Complexes Using Ion-Gel Technique - Pham, Huynh Mai; Nguyen, Thuong Nhan Phu; Van, Chi Khang; Mai, Huynh Cang (Universitas Gadjah Mada, 2024)
In this study, the alginate/chitosan complexes were prepared to encapsulate lemongrass essential oils (Cymbopogon citratus). Essential oils are secondary metabolites that are easily changed under environmental influences (temperature, pH, light). This research opened a new line in protecting essential oils from adverse effects from the surrounding environment. The ion-gel encapsulation technique combined with alginate/chitosan complexes has been applied to encapsulate C. citratus essential oil. The factors were surveyed including homogenization time (10–20 min), concentration of Tween 80 (0–5% w/w), concentration of sodium alginate (1.5–3.5% w/v), concentration of essential oils (20–40% w/w), concentration of CaCl2 (1.0–2.5% w/v), concentration of chitosan (0.5–2.0%), and pH of chitosan solution (4–6). The properties of products have been determined including moisture content as 80.39%, encapsulation yield as 98.79%, encapsulation efficiency as 88.74% with homogenization time as 15 min, concentration of Tween 80 as 1.5%, concentration of sodium alginate as 2.5% (w/v), concentration of essential oils as 30% (w/w), concentration of CaCl2 as 2.5% (w/v), concentration of chitosan as 2.0% (w/w), and pH chitosan solution as 5. The main chemical compositions of essential oils before and after encapsulation, such as citral, myrcene, and limonene, have still remained.